ASSOCIATION BETWEEN SOCIAL MEDIA AND MENTAL HEALTH CHANGES AMONG GEN-Z IN BATAM, INDONESIA: A CROSS-SECTIONAL STUDY - Tang, Kelvin; Hilton, Chelsea; Yunita, Risna; Walvinson, Riyaldi; Paerin (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2024)
Background: This study explores the association between YouTube usage and the mental health status of Gen-Z, focusing on the roles of social anxiety and parasocial interaction in YouTube addiction. Purpose: To identify the link between social anxiety (LSAS) and parasocial interaction (PSI) and YouTube addiction (IAT), while also evaluating the role of social support (MSPSS). Methods: Data were collected from 380 respondents in Batam City. The measurement tools included the Internet Addiction Test (IAT), LieBowltz Social Anxiety Scale (LSAS), Parasocial Interaction (PSI), and the Multidimensional Scale of Perceived Social Support (MSPSS). Results: Multiple regression analysis revealed that 84.5% of the variability in YouTube addiction can be explained by LSAS, PSI, and MSPSS. The F-test results indicated high significance (F = 681.862, p < 0.05). The t-test showed that LSAS (B = 0.609, t = 11.623, p < 0.0001) and PSI (B = 0.707, t = 6.642, p < 0.0001) had a significant influence on IAT, while MSPSS was not significant (B = 0.067, t = 0.893, p = 0.372). The regression model for IAT was IAT = -2.151 + 0.609LSAS + 0.707PSI + 0.067MSPSS, and for PSI was PSI = -2.715 + 0.517LSAS. Conclusion: Confirm that social anxiety and parasocial interaction significantly affect YouTube addiction, while social support does not show a significant influence. Abstrak Latar Belakang: Penelitian ini mengeksplorasi hubungan penggunaan YouTube dengan kesehatan mental anak-anak Gen-Z, dengan fokus pada peran kecemasan sosial dan interaksi parasosial dalam kecanduan YouTube. Tujuan: untuk mengidentifikasi hubungan antara kecemasan sosial (LSAS) dan interaksi parasosial (PSI) dengan kecanduan YouTube (IAT), serta mengevaluasi peran dukungan sosial (MSPSS). Metode: Data dikumpulkan dari 380 responden di Kota Batam. Alat ukur yang digunakan mencakup Internet Addiction Test (IAT), LieBowltz Social Anxiety Scale (LSAS), Parasocial Interaction (PSI), dan Multidimensional Scale of Perceived Social Support (MSPSS). Hasil: Analisis regresi berganda mengungkapkan bahwa 84,5% variabilitas kecanduan YouTube dapat dijelaskan oleh LSAS, PSI, dan MSPSS. Hasil uji F menunjukkan signifikansi tinggi (F = 681,862, p < 0,05). Uji t menunjukkan bahwa LSAS (B = 0,609, t = 11,623, p < 0,0001) dan PSI (B = 0,707, t = 6,642, p < 0,0001) memiliki pengaruh signifikan terhadap IAT, sedangkan MSPSS tidak signifikan (B = 0,067, t = 0,893, p = 0,372). Model regresi untuk IAT adalah IAT = -2,151 + 0,609LSAS + 0,707PSI + 0,067MSPSS, dan untuk PSI adalah PSI = -2,715 + 0,517LSAS. Kesimpulan: Kecemasan sosial dan interaksi parasosial berpengaruh signifikan terhadap kecanduan YouTube, sedangkan dukungan sosial tidak menunjukkan pengaruh signifikan.